Rational emotive behavior therapy in reducing of bullying behaviour among student - Ratna Juwita Wulandari (Indonesian Institute for Counseling, Education and Theraphy, 2021)
Violence in schools is increasingly prevalent today, as seen from the increasing number of reports of violence in print and on television. One example of acts of violence that occur in schools is bullying. Bullying is an act of using power to hurt someone or a group of people both verbally, physically, and psychologically so that the victim feels depressed, traumatized, and helpless. The problems that are more likely to be suffered by children who are victims of bullying include the emergence of various mental problems such as depression, insecurity while in the school environment, and a decrease in enthusiasm for learning and academic achievement. Bullying victims have poor social adjustments that make victims feel afraid to go to school and don't even want to go to school, withdrawing from relationships, so that later it will have an impact on the learning achievements of bullying victims. The method used is descriptive qualitative. This research can be done with an approach (REBT), the Rational Emotive Behavioral Therapy counseling approach is an approach that aims to change the irrational beliefs of clients (which have an impact on emotions and behavior) to be rational.